The Urban Church Imagined : Religion, Race, and Authenticity in the City - Barron, Jessica M.; Williams, Rhys H. (Book collections on Project MUSE., 2017)
Drawing on nearly two years of ethnographic data and 55 qualitative interviews, this work examines the ways in which race, class, gender, and consumption intersect with an urban context to shape the goals, identity, and experiences of a new religious congregation in Chicago.